Optimalisasi Kinerja Simpang Tiga Bersinyal Jl. Tjilik Riwut – Jl. Hiu Putih di Kota Palangka Raya - Febri Diyah Prihatiningrum; Salonten; Murniati (Program Studi Teknik Sipil Fakultas Teknik Universitas Palangka Raya, 2023)
The intersection becomes a meeting point between two or more road sections so it becomes a point of conflict.Signalized intersections are one of the controls, but the problem is often found in long queues so that vehiclesare delayed longer as a result, the intersection performance is not optimal. This study aims to analyze theperformance of the Jl. Tjilik Riwut – Jl. Hiu Putih and recommend alternative optimal solutions. Researchlocation at the intersection of Jl. Tjilik Riwut – Jl. Hiu Putih. The research was carried out for 7 days from 11July 2022 – 17 July 2022. The research method was direct surveys in the field to obtain primary data in theform of intersection geometric data, environmental conditions around the intersection, traffic flows, phases,and signal times. Secondary data in the form of population data for the city of Palangka Raya was obtainedfrom the Central Bureau of Statistics. Analysis according to Indonesia Road Capacity Guidelines (2014). Dataanalysis techniques using Microsoft Excel. The results showed that the performance of the intersection was notgood based on the Service Level (ITP E) in the existing conditions with a delay of 54.1 seconds/cur. The optimalalternative solution is alternative VI of the LrsJT Application in the Western Two-Phase Approach andproduces the smallest delay.